Strategy empowerment for the enhancement of digital literacy in public higher education: A provincial case in China - Jin, Jiepei; Siribanpitak, Pruet; Chaemchoy, Sukanya (Edelweiss Applied Science and Technology, 2025)
This study aimed to address a critical gap by developing a strategic academic management strategy to systematically enhance digital literacy within public universities. Employing a sequential mixed-methods design, the research utilized a systematic SWOT analysis, collecting survey data from 190 academic leaders, to map internal capabilities against external influences. The analysis, detailed in the findings, identified Learning Media and Resources (PNImodified: 0.775) as the most significant overall internal weakness, particularly in digital awareness, while Measurement and Evaluation (PNImodified: 0.515) was the greatest strength. Externally, political factors (PNImodified: 0.541) emerged as the leading overall threat, contrasted by technological factors (PNImodified: 0.456) as the primary overall opportunity. These quantitative findings were systematically synthesized into a robust strategic quadrant matrix, which generated four essential strategic clusters SO, WO, ST, and WT to guide institutional action. The subsequent discussion elaborates on how this matrix facilitates the formulation of aggressive, turnaround, defensive, and cautious strategies, providing a contextually grounded and operationally actionable roadmap for academic leadership to proactively cultivate digitally literate graduates equipped for the modern workforce. Ultimately, the findings underscore the potential of academic management innovation to cultivate digitally competent graduates and strengthen institutional competitiveness in the era of rapid technological advancement.